Legal Analysis of Legal Certainty of Land Ownership Rights for Foreign Citizens (WNA) in Indonesia - Maemunah, Siti; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to analyze: 1) Legal certainty of land ownership rights for foreign nationals (WNA) in Indonesia. 2) Legal consequences of the transfer of land ownership rights covertly by foreign nationals (WNA). This type of research is included in the scope of normative legal research. The approach method in this study is the statute approach. The types and sources of data in this study are secondary data obtained through literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) Legal certainty of land ownership rights for foreign nationals (WNA) in Indonesia is strictly regulated by the Basic Agrarian Law (UUPA) and its implementing regulations. According to Article 42 of the Basic Agrarian Law (UUPA), WNA can only be given use rights and lease rights to land, not ownership rights. In addition, Article 52 paragraph (1) of Law Number 1 of 2011 concerning Housing and Residential Areas (as amended by Law Number 6 of 2023) emphasizes that foreign nationals can occupy houses with rental rights or usage rights. The main criteria for foreign nationals to own a house with rental rights or usage rights is the ownership of valid immigration documents in accordance with the regulations. The usage rights and rental rights system limits foreign nationals from having full control over a house or land, in accordance with Article 21 and Article 26 of the UUPA. 2) The legal consequences of the transfer of land ownership rights in a disguised manner by foreign nationals (WNA) have serious legal implications, considering that this violates the basic principles of the Basic Agrarian Law (UUPA) which limits land ownership rights only to Indonesian Citizens (WNI). Hidden agreements, such as nominee agreements, which aim to circumvent the provisions of agrarian law, are therefore considered null and void according to Article 26 paragraph (2) of the UUPA. As a result, the promised land will fall to the state, and the parties involved cannot demand a refund. This kind of agreement is contrary to the valid conditions of an agreement according to Article 1320 of the Civil Code, especially regarding the object of the agreement and the purpose that does not conflict with the law.